Influence of a biasing stress on the SAW velocity on piezoelectric substrate - D. GAFKA (Archives of Acoustics)
The nonlinear differential equations and boundary conditions in small-field variables, for small fields superposed on large static biasing states, are obtained from general invariant nonlinear electroelastic equations. The influence on Surface Acoustic Wave (SAW) velocity of prestress (six independent tensor coefficients) is analyzed. Biasing stress tensor is involved directly into equations of motion, and the linearization about the static state is done. Change of mass density as well as the effective elastic constants of the piezoelectric substrate as a consequence of prestress is taken into account. Numerical results, given SAW velocity on prestressed substrate for different direction of stress and wave propagation are obtained for lithium niobate. Developed theory and numerical program may be useful for analyzing and designing SAW sensors of temperature, pressure, acceleration and stress.